Contribution of primary and secondary sources to organic aerosol and PM2.5 at SEARCH network sites. - Kleindienst TE*; Lewandowski M; Offenberg JH; Edney EO; Jaoui M; M* Zheng; X Ding; Edgerton ES (Journal of the Air & Waste Management Association (1995), 2010)
Chemical tracer methods for determining contributions to primary organic aerosol (POA) are fairly well established, whereas similar techniques for secondary organic aerosol (SOA), inherently complicated by time-dependent atmospheric processes, are only beginning to be studied. Laboratory chamber experiments provide insights into the precursors of SOA, but field data must be used to test the approaches. This study investigates primary and secondary sources of organic carbon (OC) and determines their mass contribution to particulate matter 2.5 microm or less in aerodynamic diameter (PM2.5) in Southeastern Aerosol Research and Characterization (SEARCH) network samples. Filter samples were taken during 20 24-hr periods between May and August 2005 at SEARCH sites in Atlanta, GA (JST); Birmingham, AL (BHM); Centerville, AL (CTR); and Pensacola, FL (PNS) and analyzed for organic tracers by gas chromatography-mass spectrometry. Contribution to primary OC was made using a chemical mass balance method and to secondary OC using a mass fraction method. Aerosol masses were reconstructed from the contributions of POA, SOA, elemental carbon, inorganic ions (sulfate [SO4(2-)], nitrate [NO3-], ammonium [NH4+]), metals, and metal oxides and compared with the measured PM2.5. From the analysis, OC contributions from seven primary sources and four secondary sources were determined. The major primary sources of carbon were from wood combustion, diesel and gasoline exhaust, and meat cooking; major secondary sources were from isoprene and monoterpenes with minor contributions from toluene and beta-caryophyllene SOA. Mass concentrations at the four sites were determined using source-specific organic mass (OM)-to-OC ratios and gave values in the range of 12-42 microg m(-3). Reconstructed masses at three of the sites (JST, CTR, PNS) ranged from 87 to 91% of the measured PM2.5 mass. The reconstructed mass at the BHM site exceeded the measured mass by approximately 25%. The difference between the reconstructed and measured PM2.5 mass for nonindustrial areas is consistent with not including aerosol liquid water or other sources of organic aerosol.